Emerging and Epizootic Fungal Infections in Animals (Springer International Publishing, 2018)
The book will provide insights into epidemic and emerging mycoses in various animal groups. The different categories of pathogens and outbreak fungi are discussed. In an introductory chapter, the reader will be provided basic information on fungal infections that are non-transmissible, infections from a common environmental source known as sapronoses, and zoophilic fungal pathogens in various animal species and populations, worldwide. Chapter 2 details the vocabulary and terminology that is required in the scientific literature in order to maintain clarity of expression to the field of Mycology. Chapters 3 to 9 discuss epidemic mycoses with a reservoir in animals and occasional outbreaks, including dermatophytoses, coccidioidomycosis, histoplasmosis, paracoccidioidomycosis, adiaspiromycosis and similar diseases, blastomycosis, and paracoccidioidomycosis ceti (lacaziosis/lobomycosis). Chapters 10 to 15 comprise emerging mycoses in animals that include feline sporotrichosis, lethargic crab disease, emergence of C. gattii in animals and zoonotic potential, white-nose syndrome in hibernating bats, chytridiomycosis in frogs and salamanders and aspergillosis in cats. The last chapter is about treatment possibilities, antifungal use in veterinary practice, and emergence of resistance. The book will address medical and veterinary mycologists, microbiologists, veterinarians, infectious disease specialists, epidemiologists, ecologists, public health scientists from academia and industry as well as graduate students, PhD students and postdocs in the field.